Determination of Energy-Optimized Locomotive Control During Train Acceleration - Kisliy, D. M.; Desiak, A. Y.; Bobyr, D. V.; Bodnar, E. B. (Science and Transport Progress, 2023)
Purpose. In this article, the authors aim to improve the mathematical model of train movement by adapting the model to determine the values of diesel power at the corresponding values of train acceleration and different modes of train operation. Based on the model, it is planned to build and analyze two-parameter dependencies of locomotive control during acceleration, which provide steady acceleration on different track profile slopes for different values of train weight, which will allow for more rational management of the locomotive fleet with strict adherence to the train schedule and minimal diesel fuel consumption for traction. Methodology. To achieve this goal, we used the method of system analysis, nonlinear programming, and numerical methods for solving differential equations of train motion, taking into account that the integration of the equation of train motion can be carried out by path, time, and speed, depending on the initially set task in traction calculations. Calculations were performed for different modes and phases of train operation. Findings. To analyze the results, we compared the obtained traction calculations, such as technical speed, travel time, and fuel consumption. To solve the problem of traction calculations, we chose the Maple software package, which allowed us not only to numerically evaluate the results of solving the two-parameter mathematical model, but also to graphically and visually, which greatly simplifies their perception. The obtained results of the calculations indicate a decrease in energy consumption. Originality. The model of train movement has been further developed, taking into account the adaptation to determine the values of diesel power consumption in the case of steady-state values of train acceleration depending on the weight of the train and the slopes of the track profile. Practical value. The expediency of the study is to save energy resources, in particular diesel fuel, for train traction and allows more accurate adherence to the train schedule, which, in turn, affects traffic safety in general.